LMS Update: Expanding into networked labor management - Mccrea, Bridget (Logistics Management (2002), 2023)
[...]very large workforces have historically been the "sweet spot" for this member of the supply chain management (SCM) software family. According to Dwight Klappich, research VP at Gartner, LMS isn't just for large food and beverage, CPG and wholesale distribution firms anymore. Defined as the expected or calculated time needed for a specific activity in any area and process in the warehouse (e.g., the time it takes to travel and execute a task), ELS are used to perform data-driven labor analysis in the warehouse. [...]McCullough says the use of automation in LMS solutions is helping organizations automate tasks like scheduling, tracking, work assignment, process engineering and performance management.